Cofilin oligomer formation occurs in vivo and is regulated by cofilin phosphorylation. - Pankaj Goyal; Dharmendra Pandey; Daniela Brünnert; Elke Hammer; Marek Zygmunt; Wolfgang Siess (PLoS ONE, 2013)
BACKGROUND: ADF/cofilin proteins are key regulators of actin dynamics. Their function is inhibited by LIMK-mediated phosphorylation at Ser-3. Previous in vitro studies have shown that dependent on its concentration, cofilin either depolymerizes F-actin (at low cofilin concentrations) or promotes actin polymerization (at high cofilin concentrations). METHODOLOGY/PRINCIPAL FINDINGS: We found that after in vivo cross-linking with different probes, a cofilin oligomer (65 kDa) could be detected in platelets and endothelial cells. The cofilin oligomer did not contain actin. Notably, ADF that only depolymerizes F-actin was present mainly in monomeric form. Furthermore, we found that formation of the cofilin oligomer is regulated by Ser-3 cofilin phosphorylation. Cofilin but not phosphorylated cofilin was present in the endogenous cofilin oligomer. In vitro, formation of cofilin oligomers was drastically reduced after phosphorylation by LIMK2. In endothelial cells, LIMK-mediated cofilin phosphorylation after thrombin-stimulation of EGFP- or DsRed2-tagged cofilin transfected cells reduced cofilin aggregate formation, whereas inhibition of cofilin phosphorylation after Rho-kinase inhibitor (Y27632) treatment of endothelial cells promoted formation of cofilin aggregates. In platelets, cofilin dephosphorylation after thrombin-stimulation and Y27632 treatment led to an increased formation of the cofilin oligomer. CONCLUSION/SIGNIFICANCE: Based on our results, we propose that an equilibrium exists between the monomeric and oligomeric forms of cofilin in intact cells that is regulated by cofilin phosphorylation. Cofilin phosphorylation at Ser-3 may induce conformational changes on the protein-protein interacting surface of the cofilin oligomer, thereby preventing and/or disrupting cofilin oligomer formation. Cofilin oligomerization might explain the dual action of cofilin on actin dynamics in vivo.